2017
DOI: 10.1111/ibi.12488
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the importance of multi‐scale management and environmental variables on moorland bird abundance

Abstract: UK moorlands are semi-natural habitats managed for a mix of livestock, game shooting and forestry, among other activities. An assessment of the importance of characteristics that correlate with moorland bird populations of high conservation importance can inform appropriate management at appropriate locations. We use hierarchical partitioning to assess the absolute and relative importance of climate, topography, soil, landscape management (wider scale habitat configuration of forestry and agriculture) and site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Grouse productivity was also higher in years with management for grouse but was not related to grazing intensity. This is consistent with other studies suggesting that predation has a stronger effect than habitat quality on population growth of Red Grouse (e.g., Thirgood et al 2002, Fletcher et al 2010, and with the positive effect of predator control on other ground-nesting birds (Pearce-Higgins and Yalden 2003, Fletcher et al 2010, Douglas et al 2014, Buchanan et al 2017, Ludwig et al 2017.…”
Section: Discussionsupporting
confidence: 92%
“…Grouse productivity was also higher in years with management for grouse but was not related to grazing intensity. This is consistent with other studies suggesting that predation has a stronger effect than habitat quality on population growth of Red Grouse (e.g., Thirgood et al 2002, Fletcher et al 2010, and with the positive effect of predator control on other ground-nesting birds (Pearce-Higgins and Yalden 2003, Fletcher et al 2010, Douglas et al 2014, Buchanan et al 2017, Ludwig et al 2017.…”
Section: Discussionsupporting
confidence: 92%
“…However, the most effective use of particular interventions requires considering their specific timing, duration, and intensity and the characteristics of the particular site or habitat. For example, due to contrasting habitat requirements, intervention responses may vary between species breeding at the same site (e.g., Buchanan, Pearce‐Higgins, Douglas, & Grant, ) and may have contrasting impacts on occupancy and abundance, productivity, and survival. Our assessment provides only a broad evaluation of the overall patterns, whereas responses are likely to vary with local context.…”
Section: Discussionmentioning
confidence: 99%
“…Among waders, such a relationship has been reported for European golden plover, northern lapwing Vanellus vanellus and Eurasian curlew (e.g., Baines, Redpath, Richardson, & Thirgood, 2008;Buchanan, Pearce-Higgins, Douglas, & Grant, 2017;Newey et al, 2016;Tharme, Green, Baines, Bainbridge, & O'Brien, 2001; see Table 1) while studies focussing specifically on Eurasian curlew have also shown a positive correlation of abundance with gamekeeper activity (Douglas et al, 2014;Franks, Douglas, Gillings, & Pearce-Higgins, 2017). Among waders, such a relationship has been reported for European golden plover, northern lapwing Vanellus vanellus and Eurasian curlew (e.g., Baines, Redpath, Richardson, & Thirgood, 2008;Buchanan, Pearce-Higgins, Douglas, & Grant, 2017;Newey et al, 2016;Tharme, Green, Baines, Bainbridge, & O'Brien, 2001; see Table 1) while studies focussing specifically on Eurasian curlew have also shown a positive correlation of abundance with gamekeeper activity (Douglas et al, 2014;Franks, Douglas, Gillings, & Pearce-Higgins, 2017).…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies have generally shown a positive relationship between grouse moor management and populations of red grouse and of ground-nesting waders. Among waders, such a relationship has been reported for European golden plover, northern lapwing Vanellus vanellus and Eurasian curlew (e.g., Baines, Redpath, Richardson, & Thirgood, 2008;Buchanan, Pearce-Higgins, Douglas, & Grant, 2017;Newey et al, 2016;Tharme, Green, Baines, Bainbridge, & O'Brien, 2001; see Table 1) while studies focussing specifically on Eurasian curlew have also shown a positive correlation of abundance with gamekeeper activity (Douglas et al, 2014;Franks, Douglas, Gillings, & Pearce-Higgins, 2017 Newey et al, 2016;Tharme et al, 2001). While crows are directly controlled on grouse moors, other species may be impacted by grouse moor management producing suboptimal habitat, relative to other upland areas that are not managed for sporting purposes.…”
Section: Introductionmentioning
confidence: 79%